Three Essays on Applications of Text Analytics in Economics - Eugenidis, Dania Margarita; Justus Liebig University Giessen (My University, 2023)
Text analytics plays an increasingly important role in various fields, including economics. Overall, text analyses can provide valuable insights into economic trends and events, helping to make better informed decisions in policy making, trend analysis and predictions. It provides a powerful tool for analyzing large amounts of mainly unstructured textual data and enlarges the spectrum of answering economic questions. It is possible to transform the field of Economics by enabling researchers to analyze unstructured, large and complex datasets and extract information in ways that have been impossible previously. In this thesis, different applications of text analytics form the core of this work: While the first paper presents a capital market analysis, the following two articles investigate a labor market related issue.
Keywords: ddc:650